Fabrication, properties and biological activity of a titanium surface modified with zinc via plasma electrolytic oxidation - Luo, Rui; Jiao, Yang; Zhang, Sujiajun; Wu, Jieshi; Wu, Xingling; Lu, Kaihang; Zhang, Pengpeng; Li, Yankun; Ni, Xiaohui; Zhao, Quanming (Frontiers in Materials, 2023)
To improve the biological activities of titanium implant surfaces and promote efficient early bone formation, the formation of bioactive coatings that promote bone formation on titanium implant surfaces is currently an important area of research. In this study, we prepared a zinc-doped porous coating (Zn-PEO) on a titanium alloy surface via plasma electrolytic oxidation. The surface characteristics of the samples were evaluated with field emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS), profilometry, static contact angles and nanoscratch studies. The slow release of zinc from the coating was detected with inductively coupled plasma‒mass spectrometry (ICP‒MS). The corrosion resistances of the samples were evaluated via electrochemical studies. On this basis, we evaluated the biocompatibility and biological activity of the sample through in vitro cell experiments. The results confirmed that a Zn-PEO coating was successfully prepared on the surface of the titanium alloy; it exhibited a porous micro/nanomorphology, and the coating and the substrate were tightly bound. The coating increased the roughness of the titanium surface and improved the wear and corrosion resistance. More importantly, the coating promoted adhesion, proliferation, differentiation and mineralization of bone marrow mesenchymal stem cells and had good biological activity. Therefore, Zn-PEO coatings with porous structures were prepared on the surfaces of titanium implants through plasma electrolytic oxidation. The Zn-PEO coating exhibited good surface properties and biological activity and has good application prospects.